1996
DOI: 10.1080/01688639608408279
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Arousal in Temporal Lobectomy: Autonomic and Performance Effects of Success and Failure Feedback

Abstract: Both theory and evidence suggest that right temporal lobectomy (RTL) patients show hypoarousal and left temporal lobectomy (LTL) patients show relative hyperarousal (Davidson, Fedio, Smith, Aurielle, & Martin, 1992). However, we hypothesized that these differences occur only under passive, nonevaluative stimulus conditions. The present study employed, instead, conditions of performance evaluation. We recorded the skin conductance responses (SCRs) and reaction times (RTs) of RTLs, LTLs, and normal controls (NCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Familiality studies showing risk ratios of 3:1 to 5:1 in children of alcoholics support this conclusion, as do twin and adoption studies demonstrating at least a 50% heritability for the disorder (Light, Irvine, & Kjerulf, 1996). In addition, recent molecular genetic studies have identified both probable markers for alcoholism and protective genes , as well as markers for addictive behavior (Davidson, Smith, Tamny, & Fedio, 1996;Thome, Gerwitz, Weijer, Wiesbeck, & Henn, 2000). It now appears that alcoholism is a quantitative disorder involving multiple genes (quantitative trait loci) that act to predispose the individual to the disease (Grisel, 2000).…”
mentioning
confidence: 51%
“…Familiality studies showing risk ratios of 3:1 to 5:1 in children of alcoholics support this conclusion, as do twin and adoption studies demonstrating at least a 50% heritability for the disorder (Light, Irvine, & Kjerulf, 1996). In addition, recent molecular genetic studies have identified both probable markers for alcoholism and protective genes , as well as markers for addictive behavior (Davidson, Smith, Tamny, & Fedio, 1996;Thome, Gerwitz, Weijer, Wiesbeck, & Henn, 2000). It now appears that alcoholism is a quantitative disorder involving multiple genes (quantitative trait loci) that act to predispose the individual to the disease (Grisel, 2000).…”
mentioning
confidence: 51%